(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The representation of autochthonous species of Polypodiophyta in Ukrainian botanical gardens and arboretums is analysed. Several fern species are recommended for further introduction with purpose of biodiversity conservation.